The pedagogical agent in online learning: the effect of the degree of realism on achievement in terms of gender. - Sahimi, Saidatul Maizura; M. Zain, Farah; Kamar, Nabila A. N.; Samar, Noorizdayantie; A. Rahman, Zuraidah; Majid, Omar; Atan, Hanafi; Fong, Soon Fook; Wong, Su Luan (Contemporary Educational Technology, 2010)
This paper describes the impact of the degrees of realism (unrealistic, moderately realistic and highly realistic) of the pedagogical agent on student’s achievement during online learning in terms of gender. Three modes of the e-learning portal with appropriate degrees of realism, namely, Online Learning with a Cartoon Pedagogical Agent (OLCPA), Online Learning with a Moderately Realistic Pedagogical Agent (OLMRPA) and Online Learning with a Highly Realistic Pedagogical Agent (OLHRPA) were developed and implemented. A quasi-experimental 3x2 factorial design was employed; independent variables were three degrees of realism, the dependent variable was achievement scores, and the moderator variable was gender of students. The subjects were 130 Form Four students (16 years old) from Malaysian secondary schools who were randomly assigned to groups. Analysis of variance (ANOVA) was employed to analyze data. The findings of the study suggest that there was no significant difference in the students’ achievement among the three degrees of realism in terms of their genders; both genders achieved almost the same across different degrees of realism. The reasons for the observed results are discussed and elaborated.